Análisis de la recaudación tributaria y su impacto en el presupuesto del Gobierno Autónomo Descentralizado Municipal del Cantón Pujilí en el período 2014-2018 - Cayo Cayo, Diana Carolina (2019)
The present investigative work had the aim to analyze the tributary collection inside the Autonomous Decentralized Government of the Pujili Canton through the study of the income budget cards, expenses and financial states, achieving by this way to know the efficiency collection grade and the impact that these one generated inside the municipality budget during the 2014 - 2018s. In the investigation the budget cards were analyzed in order to identify the efficiency percentage through a comparative chart of annual collections and the development of a signaling that allows to know the efficiency level, and later propose a collection forecast for the 2019 achieving a collection approach which the municipality will obtain during this fiscal period. The proposed investigation was made through an application methodology with a quantitative approach of experimental and explanatory type, in the deductive method there were used some investigative techniques such as the interview and the documentary revision that allowed to obtain the information for the correct development of the project. The results obtained allowed us to identify shortcomings in tax collection and how the Autonomous Decentralized Government of Canto Pujilí continues to forecast values of taxes that have not been collected in previous years and are recorded as receivables, which is why the level of collection is medium what requires an adequate financial management that allows a planning and sustainability of the different projects aimed at sustaining the progressive demand of public goods and services and through them improve the condition of life of society.